hESCs‐derived Organoids Achieve Liver Zonation Features through LSEC Modulation - Yuying Zhang; Chenyan Huang; Lei Sun; Lyu Zhou; Yudi Niu; Kaini Liang; Bingjie Wu; Peng Zhao; Zhiqiang Liu; Xiaolin Zhou; Peng Zhang; Jianchen Wu; et al. (Advanced Science)
Abstract Liver zonation, essential for diverse physiological functions, is lacking in existing organoid models, hindering their ability to recapitulate liver development and pathogenesis. Addressing this gap, this work explores the feasibility of achieving zonated organoid by co‐culturing human embryonic stem cells (hESCs) derived hepatocytes (HEP) with hESCs derived liver sinusoidal endothelial cells (LSECs) exhibiting characteristics of either the liver lobule's pericentral (PC) or periportal (PP) regions. Introducing zonated LSECs with variable WNT2 signaling subtly regulate hepatocyte zonation, resulting in noticeable metabolic function changes. Considering the lipid metabolism variations in PC and PP organoids, this work constructs biomimetic zonated metabolic dysfunction‐associated steatotic liver disease (MASLD) organoids and revealed that glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) directly target LSECs, indicating potential therapeutic mechanisms of GLP‐1RA in MAFLD alleviation. This study highlights the crucial role of non‐parenchymal cells in organoids for recapitulating niche heterogeneity, offering further insights for drug discovery and in vitro modeling of organ heterogeneity.